2019
DOI: 10.1007/s12576-019-00720-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between 26S proteasome and mitochondria in human mesenchymal stem cells’ ability to survive under hypoxia stress

Abstract: Mesenchymal stem cells (MSCs) are regarded as unique cells which play an imperative role in the field of regenerative medicine. They are characterized by the self-renewal capacity, multi-lineage differentiation abilities and immunomodulation properties which render them perfectly ideal cell type for treating a wide range of chronic diseases. Despite these enchanted features, there are many hurdles that need to be circumvented to ensure their long-term survival and viability after transplantation. Recently, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, the efficacy of MSCs is limited due to the poor survival rate after transplantation (Sylakowski et al 2020 ). Many studies have shown that MSCs are able to tolerate moderate hypoxia, but not the severe hypoxia that predominates in many diseases involving injured tissue (Sylakowski et al 2020 ; Khasawneh et al 2019 ). Under physiological conditions, MSCs can experience low O 2 concentrations ranging from 1 to 15% in their niche.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…However, the efficacy of MSCs is limited due to the poor survival rate after transplantation (Sylakowski et al 2020 ). Many studies have shown that MSCs are able to tolerate moderate hypoxia, but not the severe hypoxia that predominates in many diseases involving injured tissue (Sylakowski et al 2020 ; Khasawneh et al 2019 ). Under physiological conditions, MSCs can experience low O 2 concentrations ranging from 1 to 15% in their niche.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…It has been demonstrated that 26S proteasome could help MSCs to resist hypoxic conditions. When MSCs are exposed to moderate hypoxia (2.5% O 2 ), 26S proteasome remains functioning and improves MSCs survival and proliferation, whereas 26S proteasome is inactivated when MSCs experience intensive hypoxia, leading to the poor function of mitochondria and less chance of longer survival (Khasawneh et al, 2019).…”
Section: Mitochondrial Proteostasis and Isrmentioning
confidence: 99%
“…Bone marrow MSCs offer great promise for the treatment of myocardial ischemia owing to the ease with which they can be isolated, cultured, and expanded while maintaining important stem cell properties [64]. Researchers initially hypothesized that transplanted MSCs would be able to differentiate into cardiomyocytes and vascular endothelial cells, but more recent evidence suggests that the majority of transplanted cells die within a month under hypoxic conditions within the ischemic microenvironment, while their differentiation cannot be effectively controlled [65].…”
Section: Msc-exos-based Therapeutic Cardiac Regenerationmentioning
confidence: 99%